Governance and group conflict - Felix Koelle (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2020)
Many situations in the social and economic life are characterized by rivalry and con ict between two or more competing groups. Warfare, socio-political con icts, political elections, lobbying, and R&D competitions are all examples of inter-group con icts in which groups spend scarce and costly resources to gain an advantage over other groups. Here, we report on an experiment that investigates the impact of political institutions within groups on the development of con ict between groups. We find that relative to the case in which group members can decide individually on their level of con ict engagement, con ict significantly intensifies when investments are determined democratically by voting or when a single group member (the dictator) can decide on behalf of the group. These results hold for both symmetric and asymmetric contests, as well as for situations in which institutions are adopted exogenously or endogenously. Our findings thus suggest that giving people the possibility to vote is not the main reason for why democracies seem to engage in less wars than autocracies. Nevertheless, when giving participants the possibility to choose which institution to adopt, we find that the voting institution is the by far most popular one as it combines the desirable features of autonomy and equality.
Keywords: D72; C72; C92; 330; Conict; competition; institutions; democracy; groups; experiment